Assessing women's satisfaction with family planning services in Mozambique. Issue 3 (8th September 2016) - Chavane, Leonardo; Dgedge, Martinho; Bailey, Patricia; Loquiha, Osvaldo; Aerts, Marc; Temmerman, Marleen
Abstract : Background: The contraceptive prevalence rate in Mozambique was estimated as 11.3% in the last Demographic and Health Survey. The impact of family planning (FP) on women's health and on the reduction of maternal mortality is well known. Methods: Acknowledging the importance of user satisfaction in the utilisation of health services, exit interviews were used to assess women's satisfaction with FP services in Mozambique. The survey, conducted in 174 health facilities, was representative at the national level, covered all provinces, and both urban and rural areas. Results: Overall, 86% of respondents were satisfied with FP services, but issues such as insufficient supplies of oral contraceptives and the low quality of healthcare provider/client interactions were given as reasons for women's dissatisfaction. Conclusion: Defined actions at the level of health service provision are needed to tackle the identified issues and ensure improved satisfaction with, and better utilisation of, FP services in Mozambique.